1997
DOI: 10.1128/aac.41.5.950
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the postantibiotic and postantibiotic sub-MIC effects of levofloxacin and ciprofloxacin on Staphylococcus aureus and Streptococcus pneumoniae

Abstract: The postantibiotic subminimum inhibitory concentration effect (PA SME) may simulate in vivo drug exposure more accurately than the postantibiotic effect (PAE) since subinhibitory concentrations of drug persist between antibiotic dosings. In this study, we compared the PAEs and PA SMEs of levofloxacin and ciprofloxacin for clinical isolates of fluoroquinolone-susceptible Staphylococcus aureus and Streptococcus pneumoniae. At two times the MIC, PAEs of levofloxacin were an average of 0.6 h longer than the PAEs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
1
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 26 publications
3
17
1
4
Order By: Relevance
“…The results obtained from this study were consistent with the conclusions of a previous report by Licata et al . (). BC‐3205, a novel semi‐synthetic pleuromutilin derivative, was studied in neutropenic murine infection model.…”
Section: Resultsmentioning
confidence: 97%
“…The results obtained from this study were consistent with the conclusions of a previous report by Licata et al . (). BC‐3205, a novel semi‐synthetic pleuromutilin derivative, was studied in neutropenic murine infection model.…”
Section: Resultsmentioning
confidence: 97%
“…The PAE and PA-SME of orbifloxacin were examined in comparison with enrofloxacin, and were performed in accordance with procedures described previously [7]. Each strain was grown in the logarithmic growth phase to a concentration of approximately 5 × 10 6 colony-forming units (CFU)/mL and was prepared for use in PAE experiments.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that MICs can affect the periods of PAE and PA-SME in bacteria. However, Licata et al [7] reported that the two strains of Staphylococcus aureus , with the same MICs, showed different PAEs and PA-SMEs. Therefore, the effect of MICs on PAEs and PA-SMEs in bacteria requires further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…study, strains with higher MICs of orbifloxacin and enrofloxacin consistently showed shorter PAE and PASME when compared to those with lower MICs [17]. In another study, two strains of Staphylococcus aureus with the same MICs showed different PAE and PASME [20]. Thus, the MIC of antibiotics was not a unique dependent factor for PASME, and the relationship of the MICs of antibiotics with PASME requires further investigation.…”
Section: Discussionmentioning
confidence: 88%